2004
DOI: 10.1081/ncn-200027641
|View full text |Cite
|
Sign up to set email alerts
|

Allele Frequency of Inosine Triphosphate Pyrophosphatase Gene Polymorphisms in a Japanese Population

Abstract: The enzyme inosine triphosphate pyrophosphatase (ITPase) catalyses the pyrophosphohydrolysis of ITP to IMP. ITPase deficiency is a clinically benign autosomal recessive condition characterised by the abnormal accumulation of ITP in erythrocytes. A deficiency of ITPase may predict adverse reactions to therapy with the thiopurine drug 6-mercaptopurine and its prodrug azathioprine. In this study, we examine the frequencies of ITPA polymorphisms in 100 healthy Japanese individuals. The allele frequency of the 94C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
2
9
1
Order By: Relevance
“…With respect to ITPA, the allele frequency of the ITPA 94C4A mutation in Korean IBD patients was 0.140, higher than that found in Europeans (0.060-0.070) and similar to the frequencies found in Japanese (0.135) and Chinese (0.15) populations. 17,18 Nevertheless, we did not find any evidence of an association between the ITPA genotype and clinical outcomes. Further research is warranted to reveal the true impact of TPMT/ITPA on the clinical efficacy of thiopurines.…”
Section: Discussioncontrasting
confidence: 52%
“…With respect to ITPA, the allele frequency of the ITPA 94C4A mutation in Korean IBD patients was 0.140, higher than that found in Europeans (0.060-0.070) and similar to the frequencies found in Japanese (0.135) and Chinese (0.15) populations. 17,18 Nevertheless, we did not find any evidence of an association between the ITPA genotype and clinical outcomes. Further research is warranted to reveal the true impact of TPMT/ITPA on the clinical efficacy of thiopurines.…”
Section: Discussioncontrasting
confidence: 52%
“…Implication of the ITPA Deficiency Mutant P32T: Cross-talk between Monomers-The observation that individuals heterozygous for the P32T mutation retained 25% ITPase activity (9) suggested that both protomers of the physiological dimer need to be intact for catalytic activity. The ITPA dimer structure presented here suggests an allosteric regulatory mechanism by cross-talk between the protomers.…”
Section: Resultsmentioning
confidence: 99%
“…The ITPA gene is orthologous to microbial genes Mj0226 , rdgB and HAM1 . Several allelic variants of the ITPA gene have been described in different human populations: the coding sequence ITPA 94C->A causing a P32T change in the corresponding protein and changes in introns, ITPA IVS2 + 21A->C, and most recently found ITPA IVS2 + 68T->C and ITPA IVS2 + 68T->G alleles 29; 30; 31; 32; 33; 34; 35. All of these variants are associated with different ranges of decreased ITPase activity.…”
Section: Introductionmentioning
confidence: 99%